PELIBATAN STAKEHOLDERS DALAM PROSES INPRES MORATORIUM IZIN PERKEBUNAN SAWIT 2016-2017: SEBUAH TINJAUAN STAKEHOLDER-BASED POLICY PUBLIC PROCESS - Riaty Raffiudin (JIPAGS (Journal of Indonesian Public Administration and Governance Studies), 2017)
This article discusses the involvement of stakeholders in the process of Instruksi Presiden Moratorium for palm oil plantation permits between 2016 and 2017 using the stakeholder-based public policy process from Altman and Petkus (1994) to answer the research question that has been posed, which is, "Has there been any involvement of stakeholders since the Instruksi Presiden Moratorium for palm oil plantation permits set up by the government in 2016?” This qualitative study using secondary data is a preliminary study for more comprehensive research. The findings of this research are the three stakeholders in the palm oil industry, the Environmental NGOs, the government as the policy maker and the palm oil business- owners including GAPKI, do not have the same definition of problems and agree on the same agenda as the first stage in response to problems in the palm oil industry. This has meant that the Instruksi Presiden Moratorium for palm oil plantation permits set by the government in 2016 has not yet been implemented. Keywords: 2016 Instruksi Presiden Moratorium for palm oil plantation permits, stakeholders involvement, stakeholder-based public policy process, palm oil